Long-Term Outcome of Cystic Lesions in the Pancreas: A Retrospective Cohort Study - Ahn, Dong-Won; Lee, Sang Hyub; Kim, Jaihwan; Yoon, Won Jae; Hwang, Jin-Hyeok; Jang, Jin-Young; Ryu, Ji Kon; Kim, Yong-Tae; Kim, Sun-Whe; Yoon, Yong Bum (Gut and liver, 2012)
The management guidelines for cystic lesions of the pancreas (CLPs) are not yet well established. This study was performed to document the long-term clinical outcome of CLPs and provide guidelines for the management and surveillance of CLPs. In this retrospective cohort study, an additional follow-up was performed in 112 patients with CLPs enrolled from 1998 to 2004 during a previous study. During follow-up for the median period of 72.3 months, the size of the CLPs increased in 18 patients (16.1%). Six of these patients experienced growth of their CLPs after 5 years of follow-up. Twenty-six patients underwent surgery during follow-up, and four malignant cysts were detected. The overall rate of malignant progression during follow-up was 3.6%. The presence of mural nodules or solid components was independently associated with the presence of malignant CLPs. Seven patients underwent surgery after 5 years of follow-up. The pathologic findings revealed malignancies in two patients. There was only one pancreas-related death during follow-up. The majority of CLPs exhibit indolent behavior and are associated with a favorable prognosis. However, long-term surveillance for more than 5 years should be performed because of the potential for growth and malignant transformation in CLPs.